Enslaved and slavery archaeology:: the arroyo Leyes case (dpto. Garay, Pcia. de Santa Fe) - Ceruti, Carlos (Centro de Estudios de Arqueología Histórica (CEAH) de la Universidad Nacional de Rosario, 2021)
Sites and archaeological materials from Arroyo Leyes are briefly described in this work. Main characteristics of pottery types dug by collectors between years 1934 and 1938 are identified, and hypothesis for their origin are proposed. The pieces are studied in relation to religious and magical practices of African origin, consistent with enslavement of Gulf of Guinea inhabitants.